2017
DOI: 10.22159/ajpcr.2017.v10i6.6161
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Delivery System of Chitosan - Diterpene Lactone Fraction of Sambiloto (Andrographis Paniculata Nees): Preparation, Characterization and in Vitro Drug Release

Abstract: Objective: This paper was aimed to study the effect of chitosan, sodium tripolyphosphate (TPP) as crosslinker, and diterpene lactone fraction of sambiloto (FDTL) from Andrographis paniculata Nees which contained 75.9% andrographolide on the characteristics of the FDTL-chitosan particulate system. Those characteristics were the physicochemical interaction, physical state, morphology, and drug entrapment efficiency. The in vitro drug release of the selected FDTL-chitosan particulate system was also evaluated. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The composition and preparation methods used in this study led to the drug entrapment efficiency (EE) of 77%, which was higher compared to the previous researches, were they were dried with spray drying methods and the EE was about 30% (Sari et al 2017). Freeze drying method could minimize drug loss during the drying process.…”
Section: Drug Content and Entrapment Efficiency Of Microparticlesmentioning
confidence: 83%
See 2 more Smart Citations
“…The composition and preparation methods used in this study led to the drug entrapment efficiency (EE) of 77%, which was higher compared to the previous researches, were they were dried with spray drying methods and the EE was about 30% (Sari et al 2017). Freeze drying method could minimize drug loss during the drying process.…”
Section: Drug Content and Entrapment Efficiency Of Microparticlesmentioning
confidence: 83%
“…The diffractograms andrographolide-chitosan microparticle formulas, and the peak of Andografolid were still visible at an angle of 2θ 9.8°, 12°, 14.8°, 15.7° with small intensity. While its diffractogram did not show sharp diffraction peaks from andrographolide, which showed that andrographolide has undergone a change in crystalline structure due to the recrystallization barriers of crosslinked chitosan (Sari et al 2017).…”
Section: X-ray Diffraction Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…Encapsulation Efficiency is another important parameter to measure the amount of encapsulated active ingredient within the microparticles. The EE% is attributed to the concentration of the polymer in the system, where an increase in polymer concentration increases the density of the system and thus assist in the formation of crosslinks (Sari et al, 2016). Table 3 shows the EE% of all the formulations.…”
Section: Encapsulation Efficiency Of Ap-cs Microparticlesmentioning
confidence: 99%